Studi Material Organik batuan Induk Sebagai Sumber Batuan Hidrokarbon Lapangan 'X' Berdasarkan Data Geokimia - Harsano Jayadi; Windi Lestari; Icha Untari Meidji; Widi Atmoko (Newton-Maxwell Journal of Physics, 2023)
The need for oil and gas has led to increased exploration to produce hydrocarbons in various basins and discover new reserves. This was also done in the Kutai basin on the eastern island of Kalimantan using a quantitative correlation between geophysical logs and rock core data and qualitative analysis by analyzing geochemical data derived from the host rock. To determine the characteristics of the hydrocarbon source rock in the three test wells, three types were analyzed, namely organic material richness, organic material type, and maturity level. For the Maau-1, Wahau-1, and Tengkawang-1 test wells, the organic material content has an excellent type to become source rock. The three wells are of medium-special hydrocarbon potential in organic material, making them very likely to produce oil and gas. As for the nature of the material content, the three wells have a mature level of the source rock, making them very potential as the  very good source rock. The need for oil and gas has led to increased exploration to produce hydrocarbons in various basins and discover new reserves. This was also done in the Kutai basin on the eastern island of Kalimantan using a quantitative correlation between geophysical logs and rock core data and qualitative analysis by analyzing geochemical data derived from the host rock. To determine the characteristics of the hydrocarbon source rock in the three test wells, three types were analyzed, namely organic material richness, organic material type, and maturity level. For the Maau-1, Wahau-1, and Tengkawang-1 test wells, the organic material content has an excellent type to become source rock. In terms of organic matter, all three wells have medium-special hydrocarbon potential and, therefore, high potential to produce oil and gas. As for the nature of the material content, the three wells have a mature level of the source rock, making them very potential as the very good source rock.